Generalized trust and regional innovation activity - Christopher-Johannes Schild (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2013)
For a cross-section of 123 European regions, we find evidence for a positive effect of generalized trust on regional innovation activity. We aim to identify causal effects by using instrumental variables from climate and soil data, drawing from recent literature on the effects of climate on historic trust levels. The popular explanation for spatial clustering of innovation by interregional knowledge spillovers is also tested. It is found that spatial clustering of innovation activity can be better explained by a positive influence of trust on innovation and spatial clustering of trust.
Keywords: O31; R11; R12; Z13; 330; Social Capital; Trust; Innovation; Regional Economics; Europe